Factors Influencing Indonesian EFL Learners’ Willingness to Speak English in Classrooms - Azwar, Taufik Akbar; Harahap, Alamsyah; Azwandi (JET (Journal of English Teaching), 2021)
In the current second language pedagogy, understanding factors that contribute to learners’ willingness to speak English in classrooms is fundamental for teachers. The aims of this present study are (1) to find out the extent to which Indonesian EFL learners are willing to speak English in classrooms and (2) to investigate the factors that influence their willingness to speak English in classrooms. A descriptive quantitative design was employed in this study. This study involved 91 English learners of the University of Bengkulu. An adapted willingness to speak English questionnaire was used to collect the data. The findings indicate that most of the learners are willing to speak English in classrooms. Furthermore, some factors are found to influence the learners’ willingness to speak, including topic familiarity, topic interest, topic preparation, topic comfort, challenging topic, group size, task familiarity, seating arrangement, gender and age of interlocutor, interlocutor familiarity, fear of making mistakes, and fear of evaluation. Therefore, several pedagogical implications for teachers have been suggested in this study.